2009
DOI: 10.1161/atvbaha.108.183210
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Exposure to LPS Increases Iron, Heme, and p22 phox Levels and NADPH Oxidase Activity in Human Aortic Endothelial Cells

Abstract: Objective-Vascular oxidative stress and inflammation are contributing factors in atherosclerosis. We recently found that the iron chelator, desferrioxamine (DFO), suppresses NADPH oxidase-mediated oxidative stress and expression of cellular adhesion molecules in mice treated with lipopolysaccharide (LPS). The objective of the present study was to investigate whether and how LPS and iron enhance, and DFO inhibits, NADPH oxidase activity in human aortic endothelial cells (HAECs). Methods and Results-Incubation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…We found that NADPH oxidase activity as well as the level of p22 phox , a subunit of the NADPH component, was decreased in adipose tissue by DFO treatment. Consistent with our observation, Li and Frei reported that DFO treatment suppressed lipopolysaccharide-induced NADPH oxidase activity via attenuation of p22 phox protein expression in vivo (27) and in vitro (28). Elemental iron is necessary for enzyme activity of NADPH oxidase (33) as well as the biosynthesis of heme proteins, including the p22 phox subunit (43).…”
Section: Discussionsupporting
confidence: 84%
“…We found that NADPH oxidase activity as well as the level of p22 phox , a subunit of the NADPH component, was decreased in adipose tissue by DFO treatment. Consistent with our observation, Li and Frei reported that DFO treatment suppressed lipopolysaccharide-induced NADPH oxidase activity via attenuation of p22 phox protein expression in vivo (27) and in vitro (28). Elemental iron is necessary for enzyme activity of NADPH oxidase (33) as well as the biosynthesis of heme proteins, including the p22 phox subunit (43).…”
Section: Discussionsupporting
confidence: 84%
“…intravenous iron preparations inhibited proliferation and promoted apoptosis of cultured endothelial cells 24,25 as well as increased MNC-endothelial adhesion in vitro 6,26 ; however, a reliable cell model for atherogenesis [27][28][29] and the exact signaling pathway have not been fully established. Li and Frei 30 have found that iron increased endothelial NOx activity and ROS production in cultured endothelial cells. Additionally, ROS is thought to induce endothelial damage through activation of NF-kB, a major redox-sensitive transcription factor that is a key regulator of cytokines, chemokines, and cellular adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In the relationship between NADPH oxidase and iron, the p22 phox subunit is identified as an important target of the antioxidant effect of iron reduction. Li and Frei (33,34) have shown that LPS or iron-induced increase of p22 phox protein and NADPH oxidase activity was suppressed by deferoxamine (DFO), an iron chelator, in mice and endothelial cells. We previously found that DFO prevented white adipocyte hypertrophy through the suppression of oxidative stress via reducing p22 phox protein expression and NADPH oxidase activity.…”
Section: Discussionmentioning
confidence: 99%